Perceived Value as a Bridge: How Social Media Marketing Drives Purchase Intention in Indonesia’s Slow Fashion Industry - Sarita Premana; Prio Utomo; Kristianus Ade Sudiyono (Return : Study of Management, Economic and Bussines, 2025)
Consumer awareness of sustainability is increasingly shaping fashion consumption, with slow fashion emerging as an alternative to fast fashion by emphasizing quality, sustainability, and social responsibility. This study investigates how Social Media Marketing influences purchase intention for slow fashion products in Indonesia through perceived customer value, including quality, price, emotional, and social dimensions. Using a quantitative approach, 332 questionnaires were distributed to respondents in Greater Jakarta who are aware of slow fashion but have never purchased it, with 302 valid responses analyzed via PLS-SEM to examine direct and indirect relationships. Findings show that SMM significantly affects all perceived value dimensions; however, only quality and emotional values have a significant impact on purchase intention, suggesting that consumers prioritize functional quality and emotional connections over price or social recognition. The results indicate that social media enhances slow fashion’s image by strengthening perceived quality and emotional engagement. Integrating sustainability education with emotional branding is recommended to boost purchase intention in Indonesia. This study explains the Stimulus, Organism, Response (SOR) framework to Indonesia’s slow fashion market and offers theoretical insights for digital marketing research and practical guidance for optimizing social media strategies.